2018
DOI: 10.1088/1361-6595/aab47e
|View full text |Cite
|
Sign up to set email alerts
|

Magnetical asymmetry effect in capacitively coupled plasmas: effects of the magnetic field gradient, pressure, and gap length

Abstract: By applying the asymmetric magnetic field to a discharge, the dc self-bias and asymmetric plasma response can be generated even in a geometrically and electrically symmetric system. This is called magnetical asymmetric effect (MAE), which can be a new method to control the ion energy and flux independently (Yang et al 2017 Plasma Process. Polym. 14 1700087). In the present work, the effects of magnetic field gradient, gas pressure and gap length on MAE are investigated by using a one-dimensional implicit parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 41 publications
1
41
0
Order By: Relevance
“…It is shown that high plasma density and thereby high ion flux can be achieved even at a very weak external magnetic field (~ 10 G) where ion energy can also be optimized simultaneously [34][35][36][37][38]. It is also reported in the literature that using magnetic field asymmetry in single-frequency CCP can independently control the ion flux and ion energy [39][40]. Later Sharma et al demonstrated that enhancement in ion flux and effective control of ion energy can be achieved by imposing a uniform transverse magnetic field in low-pressure singlefrequency CCP [41].…”
Section: Introductionmentioning
confidence: 95%
“…It is shown that high plasma density and thereby high ion flux can be achieved even at a very weak external magnetic field (~ 10 G) where ion energy can also be optimized simultaneously [34][35][36][37][38]. It is also reported in the literature that using magnetic field asymmetry in single-frequency CCP can independently control the ion flux and ion energy [39][40]. Later Sharma et al demonstrated that enhancement in ion flux and effective control of ion energy can be achieved by imposing a uniform transverse magnetic field in low-pressure singlefrequency CCP [41].…”
Section: Introductionmentioning
confidence: 95%
“…Other recent studies devoted to CCP operation in the presence of an external magnetic field 26,27,34 , have explored somewhat different effects. S. Yang et al 35,36 have used an asymmetric magnetic field with variable gradients to create asymmetry in the configuration of a CCP device. Their particle simulation studies show that the magnetic field asymmetry provides a means of independently controlling the ion flux and ion energy.…”
mentioning
confidence: 99%
“…The plasma uniformity can also be tuned by adjusting the discharge asymmetry, which can be formed either geometrically, [175][176][177] electrically, [178][179][180][181] or magnetically. [182][183][184][185] In a large-area, dual-frequency (40.68 MHz/81.36MHz) CCP in hydrogen, Schüngel et al [181] demonstrated that the lateral inhomogeneities caused by SWEs can be mitigated by changing the discharge symmetry via the electrical asymmetry effect (EAE), i.e., by tuning the phase shift between the two applied frequencies. However, the underlying mechanism of the influence of discharge symmetry on the nonlinear harmonics and standing waves was not clarified.…”
Section: Methods To Optimize the Plasma Uniformitymentioning
confidence: 99%